Conclusion: Which policy space in the international trade arena can support development and food security? - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2017)
In November 2001, seven years after the creation of the World Trade Organization (WTO) and only two months after the deadly terrorist attacks of September 11, 2001, trade ministers gathered in Doha, Qatar, to launch a new round of trade negotiations aimed at lowering trade barriers and establishing rules for those barriers remaining in place. The Doha Round was ambitious, both because it proposed to cover an extensive set of topics (agriculture, industry, services, intellectual property, rules, trade facilitation, environment, geographical indications, and so on) and because it included an expanded WTO membership (the number of countries involved in the WTO grew from 128 members at the signing of the Marrakesh Declaration in 1994 to 162 on November 30, 2015; see Chapter 2). Designing an agreement that satisfies so many countries has proven to be an almost impossible challenge, particularly since barriers to trade are unequally high among sectors in these countries (see Chapter 3). The Doha Round was semiofficially